Preparation method and application of photo-thermal antibacterial hydrogel for MRSA (Methicillin Resistant Staphylococcus Aureus) infected diabetes wound
By doping dopamine into the hydrogel to modify ZIF-8 nanoparticles, COG-Z@P hydrogel was prepared, which solved the problem of single hydrogel components and insufficient antibacterial ability in the prior art, and achieved MRSA infection Efficient sterilization and rapid healing of diabetic wounds.
Patent Information
- Application Number
- CN202411458508.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
AI Technical Summary
In the prior art, the hydrogel components used for MRSA-infected diabetic wounds are relatively single, and they fail to fully cope with complex physiological problems in wound healing. They also have insufficient treatment effect on infected wounds, have long molding time and inaccurate control of light conditions. , limited antibacterial ability.
Using a composite hydrogel based on the dual crosslinking of carboxymethyl chitosan (CMCS), gelatin (Gel) and oxidized sodium alginate (OSA), doping dopamine-modified ZIF-8 nanoparticles with photothermal properties (ZIF- 8@PDA), COG-Z@P hydrogel was prepared through Schiff base reaction, which has good biocompatibility, mechanical properties and antibacterial properties.
COG-Z@P hydrogel efficiently kills bacteria under near-infrared light, has excellent antibacterial, anti-inflammatory, hemostasis and pro-healing properties, can quickly inhibit MRSA infection and shorten the healing time of chronic diabetic wounds, and improve wound prognosis.
Smart Images

Figure CN119280466A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological tissue engineering, and in particular to a preparation method and application of a photothermal antibacterial hydrogel for treating MRSA-infected diabetic wounds. Background Art
[0002] Diabetes is a complex chronic disease involving multiple pathophysiological mechanisms, often accompanied by serious complications. Studies have shown that hyperglycemia can lead to vascular lesions and nerve damage, making the wounds of diabetic patients more susceptible to bacterial infection, thereby delaying wound healing and even leading to amputation. Although antibiotics are a common strategy for treating bacterial infections, their irrational or excessive use has led to the emergence of multidrug-resistant (MDR) strains. Therefore, there is an urgent need to develop alternative treatment options with new mechanisms and low resistance potential. In addition, due to the intensification of bacterial resistance problems and their ability to survive under the protection of biofilms, single antimicrobial therapies often fail to achieve the expected therapeutic effects.
[0003] In recent years, hydrogels have attracted extensive attention due to their excellent shape adaptability, wear resistance, tissue adhesion and biological effects, showing great potential in dynamic wound dressings. At the same time, hydrogels based on natural polymers can effectively prevent wound infection and dryness due to their good biocompatibility and ability to promote cell adhesion and proliferation, and are widely used in wound treatment. Carboxymethyl chitosan (CMCS) hydrogel has become an ideal wound dressing due to its excellent biocompatibility, antibacterial activity and adjustable mechanical properties. It can effectively moisturize, form a breathable and moist environment, promote skin healing, and further enhance the therapeutic effect by combining with nanomaterials or growth factors. However, its antibacterial and healing-promoting abilities are limited. Gelatin (Gel) hydrogel promotes cell adhesion and migration with its good biocompatibility, degradability and RGD sequence, but has problems of poor adhesion and easy tearing, which limits its effectiveness. Oxidized sodium alginate (OSA) hydrogel has shown significant prospects in skin healing and tissue engineering due to its excellent biocompatibility, degradability and high water absorption capacity. Through Schiff base reaction with chitosan and gelatin, OSA hydrogel forms a stable covalently cross-linked network with enhanced mechanical strength, adhesion, antibacterial and pro-healing properties, demonstrating its potential in wound healing and tissue regeneration.
[0004] In recent years, photothermal antibacterial technology has been widely used in many fields due to its advantages of high efficiency, safety and environmental protection. This technology uses light energy to excite photothermal materials and converts light energy into heat energy to kill bacteria and viruses. Its advantages include high sterilization, good selectivity, strong controllability, environmental friendliness, high stability and reusability of materials. With the development of materials science and nanotechnology, the application prospects of photothermal antibacterial will be broader. Dopamine and its derivatives are widely used to enhance the performance of photothermal hydrogels due to their significant photothermal properties and excellent bioadhesion of polydopamine. Dopamine can combine with the matrix through its phenolic hydroxyl and amino structures to improve the mechanical strength and tissue adhesion of the hydrogel. At the same time, its photothermal properties produce local thermal effects under near-infrared light irradiation, enhance antibacterial activity, promote angiogenesis and tissue repair, and provide a new way for multifunctional treatment. ZIF-8 (metal organic framework material, Zeolitic Imidazolate Framework-8) has become a hot topic in recent years due to its porous structure, high specific surface area and excellent biocompatibility. ZIF-8 can effectively inhibit the growth of pathogens by destroying bacterial cell membranes and producing reactive oxygen species, thereby reducing the risk of wound infection.
[0005] The prior art discloses the preparation and application of a transparent photothermal antibacterial hydrogel patch. The hydrogel patch includes a base hydrogel and a photothermal conversion material dispersed therein, which can heat up under light through the photothermal effect to kill bacteria, provide a moist environment suitable for healing, and isolate the wound from the outside world to prevent pathogen invasion. The patch can generate heat under the irradiation of a light source (such as sunlight) to promote blood flow and cell regeneration. However, the prior art has the problem that the molding time exceeds 10 minutes, the frequency and time control in the illumination conditions are not accurate, the photothermal conversion efficiency and antibacterial ability are significant but limited, and the treatment effect on infected wounds is insufficient. At the same time, the prior art also discloses the preparation and application of a glycyrrhizic acid / carbon nanozyme injectable antibacterial hydrogel. The hydrogel is loaded with glycyrrhizic acid by in-situ coating technology, and carbon nanozymes are modified on its surface to give it antibacterial and anti-inflammatory functions. Through near-infrared light regulation, the hydrogel achieves the synergistic antibacterial effect of drugs and photothermal, reduces the use of antibacterial drugs and reduces the risk of drug resistance. Carbon nanozymes mimic the enzymatic activity of superoxide dismutase (SOD) and catalase (CAT), remove excess reactive oxygen species (ROS), effectively relieve inflammation, and promote the healing of wounds infected with multiple bacteria. However, the composition of hydrogels is relatively simple and fails to fully address the complex physiological problems in wound healing.
[0006] There is an urgent need in this field to develop a wound dressing that can be used in a full-thickness skin wound infection model, has better bactericidal and antibacterial effects, and has better self-repair and healing effects, and has good biocompatibility, biodegradability and hemostatic ability. Summary of the invention
[0007] In view of the shortcomings of the above-mentioned background technology, the present invention mainly solves the problem that the composition of hydrogel is relatively single and fails to comprehensively deal with the complex physiological problems in wound healing. The present invention provides a preparation method and application of photothermal antibacterial hydrogel for MRSA-infected diabetic wounds. The injectable antibacterial hydrogel prepared by the method is a composite hydrogel, which is prepared by double cross-linking of carboxymethyl chitosan (CMCS) and gelatin (Gel) with oxidized sodium alginate (OSA). Its photothermal performance mainly comes from the doping of dopamine-modified ZIF-8 nanoparticles (ZIF-8@PDA) with photothermal properties. Gel has good biocompatibility while enhancing the mechanical properties of the hydrogel. Multiple covalent bonds and non-covalent bonds can give the hydrogel dressing flexible mechanical strength, strong adhesion, good self-healing performance, and adapt to dynamic wounds with high-frequency movement. Under near-infrared (NIR) light conditions, the material can heat up through photothermal conversion and then kill bacteria. When the hydrogel is applied as an in vivo wound dressing, it has excellent antibacterial and anti-inflammatory effects, good biocompatibility, safety and degradability, and is expected to inhibit MRSA infection and accelerate the dynamic healing of infected wounds.
[0008] The first object of the present invention is to provide a method for preparing a photothermal antibacterial hydrogel for treating MRSA-infected diabetic wounds, comprising the following steps: Preparation of ZIF-8@PDA nanoparticles; The ZIF-8@PDA nanoparticles were evenly dispersed in a carboxymethyl chitosan solution, and a gelatin solution was added. After mixing evenly, the mixture was added to an oxidized sodium alginate solution, and a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds was obtained through a Schiff base reaction.
[0009] Preferably, the mass concentration of the carboxymethyl chitosan solution is 1-3%; The mass concentration of the gelatin solution is 5-20%; The mass concentration of the oxidized sodium alginate solution is 10-20%; The volume ratio of the carboxymethyl chitosan solution, the gelatin solution and the oxidized sodium alginate solution is (1-1.5): (0.5-1.5): (1.5-3).
[0010] Preferably, the oxidized sodium alginate solution is prepared by dispersing freeze-dried oxidized sodium alginate in deionized water, wherein the oxidized sodium alginate is prepared by dispersing sodium alginate in deionized water, adding sodium periodate solution, performing a light-protected reaction, and then dialyzing and freeze-drying; The oxidation degree of the oxidized sodium alginate is 27.6%.
[0011] Preferably, the concentration of ZIF-8@PDA nanoparticles in the hydrogel is 50-200 μg / mL.
[0012] The diameter distribution of the ZIF-8@PDA nanoparticles is 600-1400 nm, the surface charge is -40~-45mV, and the -1 (FTIR) has the characteristic absorption peak of catechol.
[0013] Preferably, the ZIF-8@PDA nanoparticles are prepared according to the following steps: The ZIF-8 nanoparticles were dispersed in deionized water, dopamine solution was added, and the reaction was carried out in the dark to obtain ZIF-8@PDA nanoparticles.
[0014] Preferably, the hydrogel is prepared by utilizing a Schiff base reaction between an aldehyde group and an amino group in a reaction system.
[0015] The second object of the present invention is to provide a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds, wherein the stress-strain range of the hydrogel is 0.01% to 385%; the adhesion strength of the hydrogel is 5.41 to 9.20 kPa; and the pore size of the hydrogel is 1.5 to 13.4 μm.
[0016] Preferably, the photothermal conversion efficiency of the hydrogel is as high as 38.2%, and the near-infrared light intensity is 1.0 W / cm -1 Under light for 5 minutes, E. coli The antibacterial rate of both MRSA and SARS is over 99%.
[0017] Preferably, the hydrogel can induce and regulate the phenotype of macrophages in vitro, leading to downregulation of the expression of the pro-inflammatory factor TNF-α and upregulation of the anti-inflammatory factor Arg-1, thereby promoting the polarization of cells to the M2 phenotype that inhibits inflammatory response.
[0018] The third object of the present invention is to provide a use of a hydrogel in preparing a drug for treating MRSA-infected diabetic wounds.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a preparation method and application of a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds; the hydrogel is prepared from carboxymethyl chitosan, gelatin, oxidized sodium alginate and dopamine-modified ZIF-8 nanoparticles by Schiff base bond crosslinking. Carboxymethyl chitosan (CMCS) has excellent biocompatibility, antibacterial activity and adjustable mechanical properties, can effectively moisturize, form a breathable and moist environment, and promote skin healing. Gelatin (Gel) hydrogel promotes cell adhesion and migration with its good biocompatibility, degradability and RGD sequence. Oxidized sodium alginate (OSA) shows significant prospects in skin healing and tissue engineering due to its excellent biocompatibility, degradability and high water absorption capacity. Through Schiff base reaction with chitosan and gelatin, OSA hydrogel forms a stable covalent cross-linked network, enhances mechanical strength, adhesion, antibacterial and healing properties, and shows potential in wound healing and tissue regeneration. The raw materials used in the present invention are mostly derived from natural biomacromolecules or obtained by fermentation, are easily available, inexpensive, environmentally friendly, and have good biocompatibility.
[0020] The COG-Z@P hydrogel prepared by the present invention has a carboxymethyl chitosan solution concentration of 1~3% (w / v), an oxidized sodium alginate solution concentration of 10~20% (w / v), a gelatin solution concentration of 5~20% (w / v), and a ZIF-8@PDA nanoparticle doping concentration of 0~300 µg / mL. The pore size of the COG-Z@P hydrogel is 1.5~13.4μm, and it has good injectability and shape adaptation properties. Its stress-strain range is 0.01%~385%; the adhesion strength of the hydrogel is 5.41~9.20kPa. The photothermal conversion efficiency of the hydrogel is as high as 38.2%, and the near-infrared light intensity is 1.0W / cm -1 Under light for 5 minutes, E. coli The antibacterial rates of both MRSA and SARS-CoV-2 were as high as over 99%. In addition, COG-Z@P hydrogel has excellent antibacterial properties, tissue adhesion, antioxidant properties, and good biocompatibility.
[0021] The present invention is aimed at more complicated MRSA-infected diabetic chronic wounds, and has excellent antibacterial properties, antioxidant properties, biocompatibility and tissue adhesion. COG-Z@P hydrogel can promote the rapid proliferation of L929 cells, and has the conditions and potential for treating infected chronic wounds. A full-thickness skin injury model of diabetic mice infected with MRSA was constructed, and near-infrared light treatment was performed using COG-Z@P hydrogel. In the early stage of wound healing, it can quickly stop bleeding and exert an antibacterial effect. In the middle stage of healing, it can upregulate the expression of the anti-inflammatory factor Arg-1 in the wound site, downregulate the expression of the pro-inflammatory factor TNF-α, induce the transformation of macrophages to the M1 anti-inflammatory phenotype, and alleviate the inflammatory state of the wound. In the late stage of healing, it promotes the expression of CD31 and VEGF in the wound site, and promotes angiogenesis and collagen deposition. COG-Z@P hydrogel greatly shortens the healing time of diabetic chronic wounds and improves the prognosis of the wound. Therefore, COG-Z@P hydrogel is a repair dressing that can be used for MRSA-infected diabetic chronic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the gelation principle of COG-Z@P hydrogel.
[0023] Figure 2 This is the microscopic SEM morphology of COG-Z@P200 hydrogel.
[0024] Figure 3 The self-healing properties, injectability and tissue adhesion of the hydrogel. (A) COG and COG-Z@P200 hydrogels were made into circular patches and cut in half. They can be reattached after 20 minutes (the obtained hydrogels remain intact after stretching); (B) COG-Z@P200 hydrogel can pass through a 27-gauge needle smoothly without clogging, indicating that it is injectable; (C) Photo of COG-Z@P200 hydrogel adhered to a human finger joint. Figure 4 The rheological test results of COG-Z@P hydrogel. (A) Frequency sweep of COG-Z@P hydrogel (G': storage modulus, G'': loss modulus); (B) Dynamic strain sweep test of COG-Z@P hydrogel; (C) Cyclic sweep test under 1% and 400% shear strain (ω = 1rad / s).
[0025] Figure 5 The photothermal properties of COG-Z@P hydrogel. (A) Photothermal curve of COG-Z@P hydrogel; (B) Temperature change image recorded by infrared thermal imager; (C) Temperature cycle curve of COG-Z@P hydrogel.
[0026] Figure 6is the antibacterial property of the hydrogel. Colony growth of surviving bacteria on agar plates after co-culture with the hydrogel; (BC) Bacterial survival rate calculated by colony counting method. ****P <0.0001.
[0027] Figure 7 This is a cell proliferation experiment of GOE hydrogel. The cell viability of L929 cells co-cultured with COG-Z@P hydrogel for 1, 2, and 3 days.
[0028] Figure 8 This is the result of the cell live / dead experiment of GOE hydrogel. Live / dead staining picture of COG-Z@P hydrogel and L929 cells co-cultured for 2 days.
[0029] Fig. 9 The blood compatibility results of GOE hydrogel. (A) Hemolytic activity test image of COG-Z@P hydrogel; (B) Hemolysis rate of hydrogel. ****P <0.0001.
[0030] Fig.10 The hemostatic properties of COG-Z@P hydrogel. (A) Photo of the hemostatic effect of COG-Z@P hydrogel on the liver; (B) Statistics of bleeding volume. ****P <0.0001.
[0031] Fig.11 This is a picture of the wound healing effect.
[0032] Fig.12 This is the result of HE staining of skin tissue sections.
[0033] Fig.13 This is the result of Masson staining of skin tissue sections.
[0034] Fig.14 is the subcutaneous degradation of COG-Z@P hydrogel.
[0035] Fig.15 is the in vivo toxicity of COG-Z@P hydrogel. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0037] The purpose of the present invention is to provide a wound dressing that can be used in a full-thickness skin wound infection model, has better bactericidal and antibacterial effects, self-repair and healing effects, and has good biocompatibility, biodegradability and hemostatic ability.
[0038] The present invention is based on the double cross-linking of carboxymethyl chitosan (CMCS) and gelatin (Gel) with oxidized sodium alginate (OSA) through Schiff base reaction, and doping with dopamine-modified ZIF-8 nanoparticles (ZIF-8@PDA) with photothermal properties to synthesize COG-Z@P hydrogel with photothermal anti-inflammatory, antibacterial, hemostatic and healing effects. The hydrogel contains CMCS, Gel, OSA and ZIF-8@PDA nanoparticles. Among them, the feed ratios are CMCS (3%, w / v), Gel (10%, w / v) and OSA (15%, w / v), and the doping concentration of Z@P nanoparticles is 200μg / mL. The pore size range of COG-Z@P hydrogel is 1.5~13.4μm, the photothermal conversion efficiency is as high as 38.2%, and the near-infrared light intensity is 1.0W / cm -1 Under light for 5 minutes, E. coli The antibacterial rates of COG-Z@P hydrogel against MRSA and SARS-CoV-2 were both above 99%. COG-Z@P hydrogel has self-healing properties and injectability, good tissue adhesion, and a gel-sol transition point of 385%. The preparation process of COG-Z@P hydrogel does not require complex equipment, has a simple process, and uses mild conditions. In addition, it does not produce by-products and is environmentally friendly.
[0039] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a photothermal antibacterial hydrogel for treating MRSA-infected diabetic wounds, comprising the following steps: Preparation of ZIF-8@PDA nanoparticles; The ZIF-8@PDA nanoparticles were evenly dispersed in a carboxymethyl chitosan solution, and a gelatin solution was added. After mixing evenly, the mixture was added to an oxidized sodium alginate solution, and a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds was obtained through a Schiff base reaction.
[0040] The mass concentration of the carboxymethyl chitosan solution is 1-3%; The mass concentration of the gelatin solution is 5-20%; The mass concentration of the oxidized sodium alginate solution is 10-20%; The volume ratio of the carboxymethyl chitosan solution, the gelatin solution and the oxidized sodium alginate solution is (1-1.5): (0.5-1.5): (1.5-3).
[0041] The oxidized sodium alginate solution is prepared by dispersing freeze-dried oxidized sodium alginate in deionized water, wherein the oxidized sodium alginate is prepared by dispersing sodium alginate in deionized water, adding sodium periodate solution, performing a light-protected reaction, and then dialyzing and freeze-drying; The oxidation degree of the oxidized sodium alginate is 27.6%.
[0042] The concentration of ZIF-8@PDA nanoparticles in the hydrogel is 50-200 μg / mL.
[0043] The diameter distribution of the ZIF-8@PDA nanoparticles is 600-1400 nm, the surface charge is -40~-45mV, and the -1 (FTIR) has the characteristic absorption peak of catechol.
[0044] The ZIF-8@PDA nanoparticles were prepared according to the following steps: The ZIF-8 nanoparticles were dispersed in deionized water, dopamine solution was added, and the reaction was carried out in the dark to obtain ZIF-8@PDA nanoparticles.
[0045] The hydrogel is prepared by utilizing the Schiff base reaction between the aldehyde group and the amino group in the reaction system.
[0046] In one embodiment, a method for preparing a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds comprises the following steps: dispersing carboxymethyl chitosan in deionized water, adding an appropriate amount of 0.1 M dilute hydrochloric acid to provide an acidic environment to help the chitosan dissolve, and obtaining a carboxymethyl chitosan solution with a concentration of 1-3% (w / v) after complete dissolution; Disperse gelatin in deionized water to a final dispersion concentration of 5-20% (w / v); Disperse sodium alginate in deionized water, add sodium periodate solution, perform light-protected reaction, and then dialyze and freeze-dry to obtain oxidized sodium alginate. Disperse the freeze-dried oxidized sodium alginate in deionized water to obtain an oxidized sodium alginate solution with a concentration of 10-20% (w / v); The ZIF-8 nanoparticles were dispersed in deionized water, dopamine solution was added, and the reaction was carried out in the dark, and then washed with deionized water for 3 times to obtain ZIF-8@PDA nanoparticles. The obtained ZIF-8@PDA nanoparticles were dispersed in deionized water to obtain 0~300 µg / mL ZIF-8@PDA solution.
[0047] ZIF-8@PDA nanoparticles were dissolved in carboxymethyl chitosan solution, gelatin solution was added and mixed, and then added to oxidized sodium alginate solution, wherein the volume ratio of carboxymethyl chitosan solution, gelatin solution and oxidized sodium alginate solution was (1~1.5):(0.5~1.5):(1.5~3). The photothermal antibacterial hydrogel for MRSA-infected diabetic wounds was obtained through Schiff base reaction, referred to as: COG-Z@P hydrogel.
[0048] The hydrogel prepared by the present invention comprises sodium carboxymethyl cellulose (CMCS), gelatin (Gel) and oxidized sodium alginate (OSA); Specifically, a method for preparing a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds comprises the following steps: (1) ZIF-8@PDA nanoparticles (200 μg / mL) were dissolved in carboxymethyl chitosan solution (3%, w / v).
[0049] (2) Add gelatin solution (10%, w / v) into step (1) and vortex to mix well.
[0050] (3) The mixture obtained in step (2) was added to oxidized sodium alginate solution (15%, w / v) and vortexed rapidly to obtain COG-Z@P hydrogel.
[0051] In another preferred embodiment, the degree of substitution of carboxymethyl chitosan is ≥80%.
[0052] In another preferred embodiment, the gelatin is Type A derived from pig skin.
[0053] In another preferred embodiment, the method further comprises slowly adding 2.0 mL (0.75 M) of sodium periodate solution to the oxidized sodium alginate obtained in step (3) in the dark, and reacting at room temperature in the dark for 2 h.
[0054] The photothermal antibacterial hydrogel for MRSA-infected diabetic wounds provided by the present invention has excellent photothermal antibacterial, anti-inflammatory and hemostatic properties, can promote the healing of MRSA-infected diabetic wounds, and discloses its preparation process. The specific preparation process includes the synthesis steps of oxidized sodium alginate and ZIF-8@PDA nanoparticles.
[0055] Preparation of oxidized sodium alginate: Weigh 1.0 g of sodium alginate (SA) and add it to 100 mL of deionized water. Stir overnight at room temperature until SA is completely dissolved. Then slowly add 2.0 mL (0.75 M) of sodium periodate (NaIO4) solution in the dark and react for 2 h in the dark at room temperature. Subsequently, add 2-5 mL of ethylene glycol to the reaction solution and continue stirring for 1 h to terminate the reaction. Finally, the solution obtained after the reaction was placed in a dialysis bag and dialyzed in deionized water for 3 days to remove the by-products in the reaction solution. During the dialysis process, the water was changed every 6 h on the first day and every 8 h for the next 2 days. After the dialysis was completed, the oxidized hyaluronic acid (OSA) solution in the dialysis bag was freeze-dried at -55 ° C to obtain a dry white sponge. The product was stored at -20 ° C for subsequent experiments.
[0056] Preparation of ZIF-8@PDA nanoparticles: ZIF-8 NPs were prepared by room temperature method. 0.089 g (0.29 mM) Zn(NO3)26H2O and 0.82 g (10 mM) 2-MIm were dissolved in 10.0 mL and 10.0 mL deionized water to form solution A and solution B, respectively. After stirring with a magnetic bar, solution A was mixed with solution B and stirred for 1 h to obtain a milky white dispersion solution, and the precipitate was collected by centrifugation. Washed with deionized water three times, centrifuged at 10,000 rpm, and dried under vacuum at room temperature to obtain ZIF-8 nanoparticles. Subsequently, 100 mg of ZIF-8 was dispersed in 200 mL of Tris-HCl solution (5 mM, pH 8.5). After dissolution, 0.2 g of dopamine hydrochloride was added and stirred at 500 rpm for 10 min. The pH was adjusted to 8.5. The mixture was stirred for 3 h at room temperature in the dark. After centrifugation, it was washed three times with distilled water to remove unpolymerized dopamine to obtain black ZIF-8@PDA particles.
[0057] Preparation of COG-Z@P hydrogel: Different proportions of ZIF-8@PDA NP (50, 100, 150, 200 µg / mL) were dissolved in CMCS and mixed evenly. Then 10% Gel (w / v) was added and mixed evenly. The mixed solution and the prepared OSA solution (15%, w / v) were vigorously stirred under vortex conditions until gelation. OSA was chemically double-crosslinked with Gel and CMCS through dynamic Schiff base reaction to form COG-Z@P hydrogel (COG hydrogel does not include ZIF-8@PDA NPs).
[0058] The second aspect of the present invention provides a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds, which has injectable and shape-adaptive properties, and the stress-strain range of the hydrogel is 0.01%~385%; the adhesion strength of the hydrogel is 5.41~9.20kPa; and the pore size of the hydrogel is 1.5~13.4μm.
[0059] The photothermal conversion efficiency of the hydrogel is as high as 38.2%, and the near-infrared light intensity is 1.0W / cm -1 Under light for 5 minutes, E. coli The antibacterial rate of both MRSA and SARS is over 99%.
[0060] The hydrogel can induce and regulate the phenotype of macrophages in vitro, leading to downregulation of the expression of the pro-inflammatory factor TNF-α and upregulation of the anti-inflammatory factor Arg-1, thereby promoting the polarization of cells to the M2 phenotype that inhibits inflammatory response.
[0061] The COG-Z@P hydrogel is formed by the Schiff base reaction between the aldehyde group and the amino group. In a specific embodiment, the COG-Z@P hydrogel is also added with dopamine-modified ZIF-8 nanoparticles (ZIF-8@PDA), the concentration of ZIF-8@PDA nanoparticles is 0-300 µg / mL, the diameter distribution is 600-1400 nm, the surface charge is -40--45 mV, and the surface charge is -40--45 mV at 1500 cm -1 (FTIR) has the characteristic absorption peak of catechol.
[0062] The concentrations of ZIF-8@PDA nanoparticles in the COG-Z@P hydrogel were 0, 50, 100, 150, and 200 μg / mL, respectively. By changing the concentration of ZIF-8@PDA nanoparticles, hydrogels with different ZIF-8@PDA nanoparticle doping concentrations were obtained, which were recorded as COG, COG-Z@P50, COG-Z@P100, COG-Z@P150, and COG-Z@P200.
[0063] The pore size of the COG-Z@P hydrogel is in the range of 1.5 to 13.4 μm, and as the concentration of ZIF-8@PDA nanoparticles increases, the porous network skeleton structure of the hydrogel becomes denser and the pore size becomes smaller.
[0064] Among the COG-Z@P hydrogels, COG-Z@P200 hydrogel has the smallest pore size, with an average pore size of 3.15 μm. The average pore sizes of COG and COG-Z@P100 are 7.10 and 5.27 μm, respectively.
[0065] The COG-Z@P hydrogel has injectable and shape-adaptive properties. The stress-strain range of the COG-Z@P hydrogel is 0.01% to 385%, and the linear viscoelastic region is 0.01% to 68.5%.
[0066] In the COG-Z@P hydrogel, the gel-sol transition points of all hydrogels are 318%, respectively.
[0067] The COG-Z@P hydrogel has good adhesion performance with an adhesion strength of 5.41-9.20 kPa. The adhesion strengths of COG, COG-Z@P100 and COG-Z@P200 are 5.41, 8.29 and 9.20 kPa respectively.
[0068] The COG-Z@P hydrogel has antioxidant properties, and the free radical scavenging rates of COG, COG-Z@P100 and COG-Z@P200 hydrogels are 73.56%, 74.27% and 75.61%, respectively.
[0069] The photothermal conversion efficiency of the hydrogel is as high as 38.2% under near-infrared light intensity of 1.0 W / cm -1 Under the condition of light, the temperature can reach 59.6℃ after 5 minutes of illumination, and the photothermal conversion efficiency is as high as 38.2%.
[0070] The COG-Z@P200 hydrogel has excellent antibacterial properties under near-infrared light intensity of 1.0 W / cm -1 Under light for 5 minutes, E. coli The sterilization rate of both MRSA and SARS reached over 99%.
[0071] The COG-Z@P200 hydrogel can induce and regulate the phenotypic transformation of macrophages in vivo, leading to the downregulation of the expression of the pro-inflammatory factor TNF-α and the upregulation of the anti-inflammatory factor Arg-1, thereby promoting the polarization of macrophages to the M2 phenotype that inhibits inflammatory responses.
[0072] The COG-Z@P200 hydrogel can promote the expression of CD31 and VEGF at the wound site, and promote angiogenesis and collagen deposition.
[0073] The COG-Z@P hydrogel provided by the present invention has excellent antibacterial and anti-inflammatory effects, good biocompatibility, safety and degradability, and can promote and shorten the healing process of MRSA-infected diabetic wounds.
[0074] A third aspect of the present invention provides use of a hydrogel in preparing a medicament for treating MRSA-infected diabetic wounds.
[0075] The COG-Z@P200 hydrogel provided by the present invention can be used as an antibacterial material, a hemostatic material, an anti-inflammatory material, a healing-promoting material or a biological tissue engineering material.
[0076] When the COG-Z@P200 hydrogel described in the present invention is used as an in vivo wound dressing, it has excellent antibacterial and anti-inflammatory effects, good biocompatibility, and is safe and degradable. The hydrogel can induce and regulate the phenotypic transformation of macrophages in vivo, leading to the downregulation of the expression of the pro-inflammatory factor TNF-α and the upregulation of the anti-inflammatory factor Arg-1, prompting macrophages to polarize to the M2 phenotype that inhibits inflammatory responses. It can also promote the expression of CD31 and VEGF at the wound site, promote angiogenesis and collagen deposition, and is expected to be used to inhibit MRSA infection and accelerate the dynamic healing of infected wounds.
[0077] The present invention is based on the double cross-linking of carboxymethyl chitosan (CMCS) and gelatin (Gel) with oxidized sodium alginate (OSA) through Schiff base reaction, and doping with dopamine-modified ZIF-8 nanoparticles (ZIF-8@PDA) with photothermal properties to synthesize COG-Z@P200 hydrogel with photothermal anti-inflammatory, antibacterial, hemostatic and healing effects. The hydrogel contains CMCS, Gel, OSA and ZIF-8@PDA nanoparticles. Among them, the feed ratios are CMCS (3%, w / v), Gel (10%, w / v) and OSA (15%, w / v), and the doping concentration of Z@P nanoparticles is 200μg / mL. The pore size range of COG-Z@P hydrogel is 1.5~13.4μm. OSA is at 1750cm -1 (FTIR) has the characteristic absorption peak of -CHO. ZIF-8@PDA nanoparticles, at 1500cm -1 There are characteristic absorption peaks of catechol.
[0078] COG-Z@P200 hydrogel has excellent photothermal performance, with a photothermal conversion efficiency of 38.2%. E. coli The antibacterial rate of two bacteria, MERS and MRSA, is as high as over 99%, and rapid antibacterial can be achieved within 5 minutes. COG-Z@P200 hydrogel has self-healing properties and injectability, good tissue adhesion, and a gel-sol transition point of 385%. In the MRSA-infected diabetic wound model, the wound closure rate of the COG-Z@P200 hydrogel group reached 98.73% on the 14th day, which can effectively promote the rapid healing of diabetic wounds infected with drug-resistant bacteria. COG-Z@P200 hydrogel has good biosafety and safely degrades subcutaneously within 14 days without toxic side effects.
[0079] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0080] Example 1 This example involves the synthesis of oxidized sodium alginate (OSA) Preparation of OSA: Weigh 1.0 g of sodium alginate (SA) and add it to 100 mL of deionized water. Stir overnight at room temperature until SA is completely dissolved. Then slowly add 2.0 mL (0.75 M) of sodium periodate (NaIO4) solution in the dark and react for 2 h at room temperature in the dark. Subsequently, add 2-5 mL of ethylene glycol to the reaction solution and continue stirring for 1 h to terminate the reaction. Finally, the solution obtained after the reaction was placed in a dialysis bag and dialyzed in deionized water for 3 days to remove the by-products in the reaction solution. During the dialysis process, the water was changed every 6 h on the first day and every 8 h for the next 2 days. After the dialysis was completed, the oxidized hyaluronic acid (OSA) solution in the dialysis bag was freeze-dried at -55 ° C to obtain a dry white sponge. The product was stored at -20 ° C for subsequent experiments.
[0081] Example 2 This example involves the synthesis of ZIF-8@PDA nanoparticles Preparation of ZIF-8@PDA nanoparticles: ZIF-8 NPs were prepared by room temperature method. 0.089 g (0.29 mM) Zn(NO3)2 6H2O and 0.82 g (10 mM) 2-MIm were dissolved in 10.0 mL and 10.0 mL deionized water to form solution A and solution B, respectively. The mixture was stirred with a magnetic bar, and solution A was mixed with solution B and stirred for 1 h to obtain a milky white dispersion solution. The precipitate was collected by centrifugation. The mixture was washed with deionized water for 3 times, centrifuged at 10,000 rpm, and dried under vacuum at room temperature to obtain ZIF-8 nanoparticles. Subsequently, 100 mg of ZIF-8 was dispersed in 200 mL of Tris-HCl solution (5 mM, pH 8.5). After dissolution, 0.2 g of dopamine hydrochloride was added and stirred at 500 rpm for 10 min. The pH was adjusted to 8.5. The mixture was stirred for 3 h at room temperature in the dark. After centrifugation, it was washed three times with distilled water to remove unpolymerized dopamine to obtain black ZIF-8@PDA particles.
[0082] Example 3 This example involves the synthesis of COG-Z@P hydrogel Preparation of COG-Z@P hydrogels: Different ratios of ZIF-8@PDA NPs (50, 100, 150, 200 µg mL −1 ) was dissolved in 3% CMCS and mixed evenly. Then 10% Gel (w / v) was added and mixed evenly. The mixed solution and the prepared OSA solution (15%, w / v) were vigorously stirred under vortex conditions until gelation. OSA was chemically double-crosslinked with Gel and CMCS through dynamic Schiff base reaction to form COG-Z@P hydrogel (COG hydrogel does not include ZIF-8@PDA NPs). Figure 1A is a schematic diagram of the gelation principle of COG-Z@P hydrogel. Figure 1 B. The state changes of different solutions before and after reaction synthesis. Before gelation, ZIF-8@PDA nanoparticles were added to CMC to form a flowable black liquid (which was then added to Gel for mixing). OSA solution is also a flowable liquid. The two solutions were mixed and stirred vigorously. Accompanied by a variety of non-covalent bond interactions, including hydrogen bonds, electrostatic forces, π-π bonds, and Schiff base bonds, the mixture quickly underwent a sol-gel transition to obtain COG-Z@P hydrogel, which was a non-flowable black solid gel (within 10 s).
[0083] The concentrations of ZIF-8@PDA nanoparticles in the prepared COG-Z@P hydrogel were 0, 50, 100, 150, and 200 μg / mL, respectively. By changing the concentration of ZIF-8@PDA nanoparticles, hydrogels with different ZIF-8@PDA nanoparticle doping concentrations were obtained, which were recorded as COG, COG-Z@P50, COG-Z@P100, COG-Z@P150, and COG-Z@P200 hydrogels.
[0084] Example 4 This example involves the morphology and structural characterization of COG-Z@P hydrogel Taking the series of COG-Z@P hydrogels prepared in Example 3 as an example, it can be observed from the scanning electron microscope image that the hydrogel presents a uniform, porous and interconnected internal network skeleton structure. The pore size of the COG-Z@P hydrogel ranges from 1.5 to 13.4 μm, and as the concentration of ZIF-8@PDA nanoparticles increases, the porous network skeleton structure of the hydrogel becomes denser and the pore size becomes smaller. The pore size of the COG-Z@P200 hydrogel is the smallest, with an average pore size of 3.15 μm. The average pore sizes of COG and COG-Z@P100 are 7.10 and 5.27 μm, respectively. Figure 2 This is the scanning electron microscopy result of COG-Z@P200 hydrogel. As indicated by the arrow, higher magnification confirms that ZIF-8@PDA exists uniformly inside the hydrogel in the form of nanoparticles.
[0085] Example 5 This example involves the self-healing properties of COG-Z@P hydrogel The transparent COG hydrogel and the black COG-Z@P200 hydrogel discs were cut into two halves, and then the semicircular hydrogels of different colors were placed in contact with each other along the cut line to observe whether they could re-form a complete circular gel under ambient conditions. Figure 3As shown in Figure A, without external intervention, the two semicircular hydrogels in physical contact successfully reassembled into a complete hydrogel with different colors after 30 minutes. The reassembled hydrogel even withstood the stretching of the tweezers in the direction perpendicular to the cutting line without breaking, showing excellent self-healing properties.
[0086] Example 6 This embodiment relates to the injectable Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, the prepared COG-Z@P200 hydrogel can be easily injected using a 27-gauge needle (diameter 0.41 mm) to write "NPU" without clogging. The COG-Z@P200 hydrogel was directly injected into water, and the hydrogel formed spiral threads and maintained a stable morphology in water. These structures indicate that the hydrogel has excellent injectability. The recoverable non-covalent bonds give the resulting hydrogel injectability and self-healing ability, providing more convenience for practical applications. The results are shown in Figure 3 As shown in B.
[0087] Example 7 This example relates to the biological tissue adhesion of COG-Z@P hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, the COG-Z@P hydrogel adhered to the joints of human fingers. During the movement of the finger joints (bending and straightening), the hydrogel adhered firmly to the skin surface without any detachment or cracking. Figure 3 As shown in C.
[0088] Example 8 This example involves the rheological properties of COG-Z@P hydrogel Dynamic frequency scanning measurements were performed on COG, COG-Z@P100, and COG-Z@P200 hydrogel samples, and the storage modulus (G') and loss modulus (G'') of the hydrogels at 37°C (physiological temperature) were measured. The G' and G'' of the COG hydrogel increased with increasing frequency, indicating physical entanglement in the reversible dynamic chemical cross-linked network. The rheological properties of the hydrogel are highly dependent on frequency, which is considered to be a key feature of dynamic covalent networks. However, the G' and G'' of the COG-Z@P100 and COG-Z@P200 hydrogel samples remained almost unchanged, mainly because the increase in the concentration of ZIF-8@PDA nanoparticles led to a greater cross-linking density and a more stable network structure. It was also noted that the storage modulus of the COG hydrogel was greater than the loss modulus throughout the test range, indicating that the hydrogel was in a stable gel state and had good gel strength. Figure 4As shown in A, at a frequency of 1 rad / s, the storage modulus (elastic modulus) of COG, COG-Z@P100 and COG-Z@P200 hydrogels are 808.21, 1040.3 and 1748.3Pa, respectively, which can indicate that with the increase of Z@P nanoparticle content, the crosslinking density increases, and the elastic modulus of the hydrogel also increases. When the strain reaches 385%, the G" of the three hydrogels is equal to G", indicating that the hydrogel is between solid and liquid. After the critical strain (strain>385%), the hydrogel is completely destroyed, as shown in Figure 4 As shown in B.
[0089] Example 9 This example involves the self-healing properties of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, the self-healing ability of the hydrogel was tested by continuous step strain tests. At the first strain of 400%, G′ decreased significantly from 2102.6 Pa to 339.24 Pa, and the hydrogel network was proved to be collapsed. At the first small strain of 1%, G′ recovered to 2081.02 Pa, indicating that most of the cross-linked network of the hydrogel had been restored. After 5 high and low strain cycle tests, the G′ and G″ values of the repaired hydrogel were similar to those of the first cycle, confirming that the COG-Z@P hydrogel has good self-healing properties, such as Figure 4 As shown in C.
[0090] Example 10 This example involves the photothermal performance of COG-Z@P200 hydrogel Taking the series of COG-Z@P hydrogels prepared in Example 3 as an example, after 10 min of near-infrared irradiation, as the concentration of Z@P NPs increased, the temperature of the system also increased (e.g. Figure 5 A), the ΔT of COG-Z@P200 is 38.4℃. The infrared thermal imager was used to monitor the 1.0 W / cm -2 , Temperature changes of COG-Z@P hydrogel at different times under 808 nm laser irradiation ( Figure 5 B), the thermal image conclusion is consistent with the temperature curve. In the repeated heating and cooling cycle experiment, after 4 "ON / OFF" cycles, the highest temperature that can be reached after near-infrared irradiation remains unchanged at the same temperature level, showing good photothermal reversibility ( Figure 5 C), demonstrating the stability of the photothermal properties of COG-Z@P200 hydrogel.
[0091] Embodiment 11 This example relates to the antibacterial properties of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, by reacting with Escherichia coli ( E. coil ) and methicillin-resistant Staphylococcus aureus (MRSA) were co-incubated to study the effect of different NIR irradiation times on the antibacterial effect of COG-Z@P200 hydrogel. Figure 6 A shows a direct photo of the bacterial colonies. The number of colonies was statistically analyzed, and it can be seen that with the addition of Z@P NPs, COG hydrogel has a significant E. coil and MRSA increased from 19.93% and 13.84% to 32.4% and 53.84% respectively ( Figure 6 BC).
[0092] Example 12 This example involves the cell compatibility of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, the cell viability of the hydrogels co-cultured with L929 cells was used to evaluate the cell compatibility of the hydrogels. All cells co-cultured with the hydrogels maintained cell viability comparable to that of the control group during the 3-day culture process, and all increased normally over time, indicating that all groups of hydrogels had no toxicity to the cells ( Figure 7 ). Results of live / dead staining experiments ( Figure 8 ) showed that most L929 cells in all groups were in a healthy growth state (green, live cells) after 1 and 2 days of culture, with almost no dead cells (red). The above results show that COG-Z@P hydrogel has good cell compatibility and can be safely used as a wound dressing for wound repair.
[0093] Embodiment 13 This example involves the blood compatibility of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, 0.1% Triton and PBS solutions were used as positive and negative controls in the hemolysis experiment. Fig. 9 As shown in A, after the hydrogel was incubated with diluted whole blood for 1 h, there was no obvious hemolysis in the COG-Z@P hydrogel group and the negative control group (the supernatant remained clear). The supernatant of the 0.1% Triton group was bright red, which was due to the leakage of hemoglobin caused by the rupture of red blood cells after hemolysis. By testing the absorbance of the supernatant at 540 nm, the hemolysis rates of COG, COG-Z@P50, COG-Z@P100, COG-Z@P150 and COG-Z@P200 hydrogels were calculated to be 0.08%, 0.01%, 0.01%, 0.03% and 0.21%, respectively ( Fig. 9B). It is far below the safe hemolysis level of 5.0%, indicating that COG-Z@P hydrogel has excellent blood compatibility.
[0094] Embodiment 14 This example relates to the hemostatic properties of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, good tissue adhesion helps to seal the wound and stop bleeding, thereby promoting wound healing. In the diabetic mouse bleeding model, the liver was punctured with a needle to induce bleeding, and then the wound was treated with a prefabricated COG-Z@P200 hydrogel patch (100 μL, 7 mm in diameter) to stop bleeding. COG-Z@P200 hydrogel significantly reduced liver bleeding ( Fig.10 A), which has the effect of closing the wound and stopping bleeding. Fig.10 As shown in B, the blood loss of the untreated control group was 246.47 mg, while the blood loss of the COG-Z@P200 hydrogel group was only 111.02 mg, indicating that the hydrogel has good adhesion and hemostatic properties.
[0095] Embodiment 15 This example relates to the healing performance of COG-Z@P200 hydrogel on MRSA-infected diabetic wounds A full-thickness skin defect was created on the back of mice to establish a subcutaneous infection model, and the wound healing status of hydrogel treatment was recorded on days 0, 3, 7, and 14. No adverse reactions occurred in all animal groups during the entire postoperative period. Fig.11 The images of skin defects treated in the Control, COG, COG+NIR, COG-Z@P200, and COG-Z@P200+NIR groups at 0, 3, 7, and 14 days are shown, among which the wound closure rates of the COG+NIR and COG-Z@P200+NIR groups were 91.87% and 98.73%, respectively, among which the wound area of the COG-Z@P200+NIR group was the smallest and almost completely healed.
[0096] H&E staining was performed on the wound tissue to analyze the histological changes of the wound. Fig.12 . By observing the results of tissue sections under a low-power microscope, on the 3rd day, a large number of inflammatory cells were observed to migrate in each group, indicating that the wounds in each group were in an inflammatory state. On the 7th day, scabs were observed in all hydrogel-treated groups, and inflammatory cells and epithelial cells began to migrate to the middle of the wound, but the appearance of new epidermis was not observed in the Control group, and signs of healing were not obvious. On the 14th day, the COG-Z@P200+NIR group had almost completed tissue remodeling, as shown by an epidermal thickness close to that of normal skin, a narrow dermal gap, a dermal layer with a relatively normal structure, and more hair follicle structures.
[0097] Masson trichrome staining was used to analyze the collagen content in wound tissue after different treatments. Fig.13 As shown. On the 7th day, the content of fibroblasts in the wounds of each group increased. The collagen fibers of the Control and COG groups were concentrated on both sides of the wound surface, while the collagen below the wound was relatively less. In the COG-Z@P200 and COG-Z@P200+NIR groups, it was observed that obvious collagen fibers were deposited in the granulation tissue, and the collagen distribution was relatively uniform. On the 14th day, the content of fibroblasts and collagen fibers in each group increased significantly. In the wound of the COG-Z@P200+NIR group, the collagen fibers showed a more orderly bundle arrangement (blue), the elastic fibers increased, the tissue structure was tight and regular, and clear neovascularization was observed (green arrows in the figure), indicating that the wound healing process was approaching the end.
[0098] Example 16 This example relates to the in vivo degradation performance of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, 100 μL of sterile saline and sterilized COG-Z@P200 hydrogels were implanted subcutaneously, and the degradation of the hydrogels at different implantation times was observed. Fig.14 The results showed that the hydrogel was almost completely degraded after 14 days. HE staining and Masson staining were used to observe the skin inflammation status at different times of subcutaneous implantation. Compared with the Control group, COG-Z@P200 had no obvious inflammatory reaction, obvious collagen deposition, and no obvious difference between the tissue site and the surrounding normal tissue at 14 days.
[0099] Embodiment 17 This example relates to the in vivo toxicity of COG-Z@P200 hydrogel Taking the series of COG-Z@P200 hydrogels prepared in Example 3 as an example, after using COG-Z@P200 hydrogels, H&E staining was used to observe the internal organs and found that ( Fig.15 ), after MRSA infection, the myocardium of the control mice ruptured (blue arrow), the hepatic sinusoidal cavity expanded (black arrow), the junction between the white pulp (WP) and the red pulp (RP) in the spleen was blurred, inflammatory infiltration appeared in the lungs (yellow circle), and the kidneys showed glomerular dilatation (yellow arrow), tubular dilatation (blue arrow), and vacuolar degeneration. After COG-Z@P+NIR treatment, the inflammatory state was improved, and the organs returned to normal without inflammatory infiltration.
[0100] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0101] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds, characterized in that: The following steps are involved: Preparation of ZIF-8@PDA nanoparticles; The ZIF-8@PDA nanoparticles were evenly dispersed in a carboxymethyl chitosan solution, and a gelatin solution was added. After mixing evenly, the mixture was added to an oxidized sodium alginate solution, and a photothermal antibacterial hydrogel for MRSA-infected diabetic wounds was obtained through a Schiff base reaction.
2. The method for preparing the photothermal antibacterial hydrogel for MRSA-infected diabetic wounds according to claim 1, characterized in that: The mass concentration of the carboxymethyl chitosan solution is 1-3%; The mass concentration of the gelatin solution is 5-20%; The mass concentration of the oxidized sodium alginate solution is 10-20%; The volume ratio of the carboxymethyl chitosan solution, the gelatin solution and the oxidized sodium alginate solution is (1-1.5): (0.5-1.5): (1.5-3).
3. The method for preparing the photothermal antibacterial hydrogel for MRSA-infected diabetic wounds according to claim 2, characterized in that: The oxidized sodium alginate solution is prepared by dispersing freeze-dried oxidized sodium alginate in deionized water, wherein the oxidized sodium alginate is prepared by dispersing sodium alginate in deionized water, adding sodium periodate solution, performing a light-protected reaction, and then dialyzing and freeze-drying; The oxidation degree of the oxidized sodium alginate is 27.6%.
4. The method for preparing the photothermal antibacterial hydrogel for MRSA-infected diabetic wounds according to claim 1, characterized in that: The concentration of ZIF-8@PDA nanoparticles in the hydrogel is 50-200 μg / mL. The diameter distribution of the ZIF-8@PDA nanoparticles is 600-1400 nm, the surface charge is -40~-45mV, and the -1 (FTIR) has the characteristic absorption peak of catechol.
5. The method for preparing the photothermal antibacterial hydrogel for MRSA-infected diabetic wounds according to claim 1, characterized in that: The ZIF-8@PDA nanoparticles were prepared according to the following steps: The ZIF-8 nanoparticles were dispersed in deionized water, dopamine solution was added, and the reaction was carried out in the dark to obtain ZIF-8@PDA nanoparticles.
6. The method for preparing the photothermal antibacterial hydrogel for MRSA-infected diabetic wounds according to claim 1, characterized in that: The hydrogel is prepared by utilizing the Schiff base reaction between the aldehyde group and the amino group in the reaction system.
7. A photothermal antibacterial hydrogel for MRSA-infected diabetic wounds prepared by the method according to any one of claims 1 to 6, characterized in that: The stress-strain range of the hydrogel is 0.01% to 385%; the adhesion strength of the hydrogel is 5.41 to 9.20 kPa; and the pore size of the hydrogel is 1.5 to 13.4 μm.
8. The photothermal antibacterial hydrogel for treating MRSA-infected diabetic wounds according to claim 7, characterized in that: The photothermal conversion efficiency of the hydrogel is as high as 38.2%, and the near-infrared light intensity is 1.0W / cm -1 Under light for 5 minutes, E. coli The antibacterial rate of both MRSA and SARS is over 99%.
9. The photothermal antibacterial hydrogel for treating MRSA-infected diabetic wounds according to claim 7, characterized in that: The hydrogel can induce and regulate the phenotype of macrophages in vitro, leading to downregulation of the expression of the pro-inflammatory factor TNF-α and upregulation of the anti-inflammatory factor Arg-1, thereby promoting the polarization of cells to the M2 phenotype that inhibits inflammatory response.
10. Use of the hydrogel according to any one of claims 7 to 9 in preparing a drug for treating MRSA-infected diabetic wounds.
Citation Information
Cited By
Implant surface modification method for diabetic bone repair
CN121102581A
RB (at) PDA hydrogel precursor for treating skin infection as well as preparation method and application of RB (at) PDA hydrogel precursor
CN121337725A